THE EFFECT OF POW+TREE STRATEGY TOWARDS STUDENTS’ WRITING SKILL - Ismawati, Ismawati; admin, admin (Teaching English as a Foreign Language Overseas Journal, 2022)
This research is aimed prove whether the POW+TREE strategy has a significant effect or not and to determine the effect of POW+TREE strategy towards students’ writing skill of UPTD SMP Negeri 6 Sinjai. This research focused as pre-experimental research one group pretest and posttest. The population of this research were the ninth-grade students of UPTD SMP Negeri 6 Sinjai, in academic year 2021/2022 consisting of 210 students. Purposive sampling technique was used to take one classes as the sample of the research which consist of 29 students. The data were obtained from writing test. The results of the research used inferential analysis of t-test by SPSS v.16, showed that there was a significant improvement in the students’ mean score writing skill between the pretest and posttest. The mean score of the students’ writing increased from 45.83 in pre-test to 82.23 in post-test. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Therefore, the hypothesis of this study was accepted. It means that the POW+TREE strategy gave significant effect on students writing skill of UPTD SMP Negeri 6 Sinjai. In addition, students’ motivation after using this strategy also increased. The researcher concludes that the effect of POW+TREE strategy in teaching English enhances the students’ writing skill.